Determination of The Essential Micro Element Content of Padina sp from Lemukutan Waters as a Biostimulant Candidate - Apindiati, Rita Kurnia; Ashari, Asri Mulya (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The search for biostimulant candidates to increase plant fertility is increasingly being encouraged, especially in utilizing abundant marine resources. Padina sp seaweed, which is widely found in Lemukutan waters, is a type of brown seaweed that is not widely used by the local community, and tends to be considered a weed. Determination of micromineral levels in Padina sp using the atomic absorption spectrophotometry method. The aim of this research is to determine the micro mineral content of iron (Fe), zinc (Zn), manganese (Mn), and copper (Cu) in Padina sp seaweed from the waters of Lemukutan Island as a biostimulant candidate. The research results show that the micro mineral elements Padina sp from Lemukutan waters contain Fe, Zn, Mn and Cu elements of 5.05 ppm, 1.3 ppm, 2.87 ppm and 0.1 ppm respectively. Based on the micro mineral content, it indicates that Padina sp can be used as a basic ingredient for biostimulants in the fields of agriculture and aquaculture.